The Effect of Insight Questions Inventory and Visual Support Strategies on Carer-Reported Quality of Life for Children With Cerebral Palsy and Perceptual Visual Dysfunction in Nigeria: A Randomized Controlled Trial - Duke, Roseline E.; Chimaeze, Torty; Kim, Min J.; Ameh, Soter; Burton, Kathryn; Bowman, Richard (Frontiers in Human Neuroscience, 2021)
Symptoms of higher visual processing problems (perceptual visual dysfunction (PVD) in children with Cerebral Palsy (CP), have been effectively identified by structured clinical history question inventory. PVD has been shown to affect quality of life and specific habilitational strategies linked to inventory responses have previously shown promise in improving quality of life. Through an RCT, based on a community based sample of children with CP in Cross River State, Nigeria, we aimed to determine if a structured history inventory such as the Insight question inventory and associated tailored visual support strategies (VSS) for the management of those children who have perceptual visual dysfunction (PVD), can improve quality of life and is superior to standard therapy. Children with CP were recruited by the key informant methodology and confirmed by clinical examination. The parent reported Insight Question Inventory was used to identify children with PVD. Primary outcome measures were Pediatric Quality of Life 4.0 generic (PedsQL) and Pediatric Quality of Life 3.0 Cerebral Palsy (PedsQL-CP) scale scores. Children were enrolled with a parallel arm allocation to either Insight Questions Inventory and visual support strategies or to standard therapy for CP. Children were followed up for 6 weeks with phone calls every week session and the questionnaires repeated at the end of the 6 weeks’ period. Results show that the children in the treatment group (n = 191) who received 6 weeks sessions of the Visual Support Strategies in the intervention showed no significantly different change between baseline and follow up in quality of life (PedsQL generic p=0.943: CI - 0.649 - 6.067 and PedsQL-CP p=0.287;CI - 6.388 - 3.551) compared to the control group. The intervention group suggested a significant improvement (p=0.035; CI -15.728 0.6199) in the PedsQL-CP subscale of speech and communication. The use of visual support strategies for the treatment of PVD in children with CP in this population does not show any superiority over current standard CP management in terms of overall quality of life but did in the area of speech and communication. Further research and refinement of these management methods is required.